Environmental Enrichment Reverses Maternal Sleep Deprivation-Induced Anxiety-Like Behavior and Cognitive Impairment in CD-1 Mice - Zhang, Yue-Ming; Cheng, Yun-Zhou; Wang, Ya-Tao; Wei, Ru-Meng; Ge, Yi-Jun; Kong, Xiao-Yi; Li, Xue-Yan (Frontiers in Behavioral Neuroscience, 2022)
Preclinical studies have clearly indicated that offspring of mothers who suffered sleep deprivation during pregnancy exhibit anxiety, depression-like behaviors, and cognitive deficits. The cognitive impairment induced by maternal sleep deprivation (MSD) is currently poorly treated. Growing evidence indicates that an enriched environment (EE) improves cognition function in models of Alzheimer’s disease, schizophrenia, and lipopolysaccharide. However, the effects of EE on hippocampal-dependent learning and memory, as well as synaptic plasticity markers changes induced by MSD, are unclear. In the present study, pregnant CD-1 mice were randomly divided into a control group, MSD group, and MSD+EE group. Two different living environments, including standard environment and EE, were prepared. When male and female offspring were 2 months, the open field test and elevated plus maze were used to assess anxiety-like behavior, and the Morris water maze was used to evaluate hippocampal learning and memory. Western blotting and real-time fluorescence quantitative polymerase chain reaction were used to detect the expression of brain-derived neurotrophic factor and Synaptotagmin-1 in the hippocampus of offspring. The results revealed that MSD-induced offspring showed anxiety-like behaviors and cognitive impairment, while EE alleviated anxiety-like behavior and cognitive impairment in offspring of the MSD+EE group. The cognitive impairment induced by MSD was associated with a decreased brain-derived neurotrophic factor and an increased Synaptotagmin-1, while EE increased and decreased brain-derived neurotrophic factor and Synaptotagmin-1 in the hippocampus of mice from MSD+EE group, respectively. Taken together, we can conclude that EE has healing effects on MSD-induced synaptic plasticity markers changes and can attenuate anxiety-like behaviors and cognitive impairment.